C–C bond coupling with sp3 C–H bond via active intermediates from CO2 hydrogenation - Qianli Ma; Jianian Cheng; Xiaojing Wu; Jin Xie; Ruihui Zhang; Zhihe Mao; Hongfang Yang; Wenjun Fan; Jianrong Zeng; Johannes Hendrik Bitter; Guanna Li; Zelong Li; et al. (Nature Communications)
Abstract Compared to the sluggish kinetics observed in methanol-mediated side-chain alkylation of methyl groups with sp3 C–H bonds, CO2 hydrogenation emerges as a sustainable alternative strategy, yet it remains a challenge. Here, as far as we know, it is first reported that using CO2 hydrogenation replacing methanol can conduct the side-chain alkylation of 4-methylpyridine (MEPY) over a binary metal oxide-zeolite Zn40Zr60O/CsX tandem catalyst (ZZO/CsX). This ZZO/CsX catalyst can achieve 19.6% MEPY single-pass conversion and 82% 4-ethylpyridine (ETPY) selectivity by using CO2 hydrogenation, which is 6.5 times more active than methanol as an alkylation agent. The excellent catalytic performance is realized on the basis of the dual functions of the tandem catalyst: hydrogenation of CO2 on the ZZO and activation of sp3 C–H bond and C–C bond coupling on the CsX zeolite. The thermodynamic and kinetic coupling between the tandem reactions enables the highly efficient CO2 hydrogenation and C–C bond coupling. In-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and density functional theory (DFT) calculations suggest that the CHxO* (CH2O*) species, rather than methanol produced from CO2 hydrogenation, is the key intermediate to achieve the C–C bond coupling.